Age and Comorbidities Predict COVID-19 Outcome, Regardless of Innate Immune Response Severity: A Single Institutional Cohort Study. (5th December 2022) - Mohan, Aditya A.; Olson, Lyra B.; Naqvi, Ibtehaj A.; Morrison, Sarah A.; Kraft, Bryan D.; Chen, Lingye; Que, Loretta G.; Ma, Qing; Barkauskas, Christina E.; Kirk, Allan; Nair, Smita K.; Sullenger, Bruce A.; et al.
Abstract : OBJECTIVES: The COVID-19 pandemic has claimed over eight hundred thousand lives in the United States alone, with older individuals and those with comorbidities being at higher risk of severe disease and death. Although severe acute respiratory syndrome coronavirus 2–induced hyperinflammation is one of the mechanisms underlying the high mortality, the association between age and innate immune responses in COVID-19 mortality remains unclear. DESIGN: Flow cytometry of fresh blood and multiplexed inflammatory chemokine measurements of sera were performed on samples collected longitudinally from our cohort. Aggregate impact of comorbid conditions was calculated with the Charlson Comorbidity Index, and association between patient factors and outcomes was calculated via Cox proportional hazard analysis and repeated measures analysis of variance. SETTING: A cohort of severely ill COVID-19 patients requiring ICU admission was followed prospectively. PATIENTS: In total, 67 patients (46 male, age 59 ± 14 yr) were included in the study. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Mortality in our cohort was 41.8%. We identified older age (hazard ratio [HR] 1.09 [95% CI 1.07–1.11]; p = 0.001), higher comorbidity index (HR 1.24 [95% CI 1.14–1.35]; p = 0.039), and hyponatremia (HR 0.90 [95% CI 0.82–0.99]; p = 0.026) to each independently increase risk for death in COVID-19. We also found that neutrophilia ( R = 0.2; p = 0.017), chemokine C-C motif ligand (CCL) 2 ( R = 0.3; p = 0.043), and C-X-C motif chemokine ligand 9 (CXCL9) ( R = 0.3; p = 0.050) were weakly but significantly correlated with mortality. Older age was associated with lower monocyte ( R = –0.2; p = 0.006) and cluster of differentiation (CD) 16+ cell counts ( R = –0.2; p = 0.002) and increased CCL11 concentration ( R = 0.3; p = 0.050). Similarly, younger patients (< 65 yr) demonstrated a rise in CD4 (b-coefficient = 0.02; p = 0.036) and CD8 (0.01; p = 0.001) counts, as well as CCL20 (b-coefficient = 6.8; p = 0.036) during their ICU stay. This CD8 count rise was also associated with survival (b-coefficient = 0.01; p = 0.023). CONCLUSIONS: Age, comorbidities, and hyponatremia independently predict mortality in severe COVID-19. Neutrophilia and higher CCL2 and CXCL9 levels are also associated with higher mortality, while independent of age.